Thienothiophene Scaffolds as Building Blocks for (Opto)Electronics - Jan Podlesný; Filip Bureš (Organics, 2022)
Thieno[3,2-b]thiophene and isomeric thieno[2,3-b]thiophene represent fused, bicyclic and electron rich heterocycles. These small planar organic compounds belong to the remarkable family of annulated building blocks for various organic materials. The first part of this review focuses on the synthesis of the primary unsubstituted thienothiophene scaffolds. All synthetic pathways available in the literature, dating from the 19th century, are summarized. The second part is devoted to the applications of the thienothiophene-derived materials across (opto)electronics. Organic light emitting diodes, organic solar cells, organic field-effect transistors and nonlinear optics were identified as the most successful application areas of both thienothiophenes. The fundamental structure-property relationships were evaluated for each particular group of derivatives.